Kuracja bólu głowy, epilepsji, chorób oczu i uszu według Skryboniusza Largusa (I w.) "Compositiones medicamentorum" – przekład - Katolo, Artur (Collectanea Philologica, 2024)
Compositiones Medicamentorum by Scribonius Largus, dating from the 1st century, is one of the most important sources of the history of medicine. The recipes contained therein were used in European medicine until the end of the 17th century. The aim of this article is to present [translated from Latin] the methods of treating headache, epilepsy and diseases of the eyes and ears according to this ancient Roman physician.